2021
DOI: 10.7196/samj.2021.v111i8.15477
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the epidemiological understanding of hepatitis C in South Africa: Perspectives from a patient cohort in a rural town

Abstract: Globally, ~71 million people are viraemic for hepatitis C virus (HCV) infection, with 10.2 million (14%) residing in sub-Saharan Africa. [1] The prevalence of HCV in South Africa (SA) is <1%, with modelled data suggesting ~600 000 infected. [2] Despite typical HCV transmission risks being present in SA, such as people who inject drugs (PWID), pre-1992 blood or blood products (before universal HCV screening was introduced into blood services), parenteral injuries in healthcare workers and traditional practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Sustained virologic response (SVR) rates of 71-77% and 64% after treatment of genotype 5 infections with pegylated interferon + ribavirin have been reported in South Africa and France, respectively [51][52][53]. DAA treatment of HCV in South Africa has been reported in a pilot study of 21 individuals [20]. The overall SVR was 95%; however, only 8 individuals with genotype 5 were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained virologic response (SVR) rates of 71-77% and 64% after treatment of genotype 5 infections with pegylated interferon + ribavirin have been reported in South Africa and France, respectively [51][52][53]. DAA treatment of HCV in South Africa has been reported in a pilot study of 21 individuals [20]. The overall SVR was 95%; however, only 8 individuals with genotype 5 were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported that HCV genotype is a determinant of treatment response and disease pathogenesis [11][12][13][14]. HCV genotype 5 was originally identified in South Africa [15,16], where it represents 35-60% of all HCV genotypes [16][17][18][19][20]. However, pockets of genotype 5 infections have been reported in France, Spain, Syria, Greece, Botswana, Ethiopia, India, and Belgium [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%